Quiet Diplomacy : Memoirs of an Ambassador of Pakistan - Marker, Jamsheed 1922-; Foreword by Wolpert, Stanley (Karachi Oxford University Press, 2010)
Ambassador Jamsheed Marker one of the most seasoned and skilful diplomats I know, with extensive UN experience, was my choice. No one had better credentials for such a difficult and delicate task. Marker's intelligence, discretion, capacity to listen, patience, perseverance and endurance, made him the right choice to resolve the protracted conflict. He listened to the Timorese people and understood their anxieties
Include Appendix and index
Keywords: Pakistan -- Diplomatic relations -- Ambassadors